Analisis Efektifitas Biaya Terapi Pengobatan Pasien Diabetes Mellitus Tipe 2 terhadap Kontrol Glukosa Darah - Ulfa, Ninik Mas; Fandinata, Selly Septi; Puspitasari, Indra (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2023)
Diabetes mellitus (DM) is a chronic disease characterized by blood glucose levels exceeding normal. The length of therapy in DM patients causes the large amount of treatment costs incurred, although in Indonesia BPJS insurance is used but this puts the burden of health financing on the Indonesian government, so there is a need for an analysis of costs associated with therapeutic outcomes. The purpose of this study was to analyze the Cost Effectiveness of Type 2 DM patients in a hospital in the South Surabaya area. The method used is observation, with retrospective observation on type 2 DM patients in outpatient internal polyclinics for the period April – December 2021. The results obtained were 30 patients who routinely controlled 2, 3, 4, 5, 6, 7, 8 and 9 months, receiving single therapy or a combination of antidiabetic drugs. In this study, a cost and effectiveness analysis was carried out with the measurement of therapeutic outcomes, namely pre-post GDP and pre-post GD2PP. The conclusion of this study were 30 female patients (100%), age > 45 years 24 people (80%). The effectiveness of sulfonylurea single therapy is 50% with an ACER of between Rp. 4,392.48 – Rp. 18,686.86 routine control 2, 3 and 9 months. For the treatment of 2 combinations of Thiazolidinediones + Insulin has an effectiveness value of 100% with ACER Rp. 42,490.08 routine control 6 months. While the 3 combinations that have a 100% effectiveness value are the combination of Sulfonylurea + Thiazolidinedione + Biguanide with an ACER price of Rp. 6,668.4 routine follow-up for 3 months. In 3 combinations of oral antidiabetic with insulin (Insulin + Sulfonylurea + Thiazolidioine + alpha glucosidase inhibitor) has a 100% effectiveness value, the ACER price is Rp. 36,082.36 routine control 7 months.